2019
DOI: 10.1177/2040622318821622
|View full text |Cite
|
Sign up to set email alerts
|

Screening and evaluation tools of dysphagia in adults with neuromuscular diseases: a systematic review

Abstract: Background:The purpose of this systematic review was to summarize the different dysphagia screening and evaluation tools, and to identify their measurement properties in adults with neuromuscular diseases (NMDs).Methods:A systematic review was performed based on the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The search strategy was conducted across three databases (PubMed, CINAHL and ScienceDirect). Measurement properties of each tools and the Quality Index, develop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(44 citation statements)
references
References 86 publications
0
39
0
Order By: Relevance
“…When investigating this topic, a gap emerges. There appears to be more literature around what tools are appropriate for the screening and assessment of dysphagic patients (Audag, Goubau, Toussaint, & Reychler, 2019 ; Sassi, Medeiros, Zilberstein, Jayanthi, & Andrade, 2017 ) compared to what criteria can be used to identify these patients by other professionals prior to a screening or assessment by an SLT. Perhaps, this is an area that needs to be developed.…”
Section: The Argumentmentioning
confidence: 99%
“…When investigating this topic, a gap emerges. There appears to be more literature around what tools are appropriate for the screening and assessment of dysphagic patients (Audag, Goubau, Toussaint, & Reychler, 2019 ; Sassi, Medeiros, Zilberstein, Jayanthi, & Andrade, 2017 ) compared to what criteria can be used to identify these patients by other professionals prior to a screening or assessment by an SLT. Perhaps, this is an area that needs to be developed.…”
Section: The Argumentmentioning
confidence: 99%
“…Published studies about swallowing problems in pediatric neuromuscular diseases were found to be performed on subgroups of NMDs. However no consensus on oro-motor and swallowing problems exists in pediatric NMDs (10)(11)(12). Thus the aim of our study was to put forth the descriptive characteristics of oral and swallowing problems in a group of pediatric NMD patients with different diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Oral function consisted of several dimensions [14][15][16][17]. e oral function of the elderly varies and covers a very wide range [18][19][20][21]. Measuring equipment and evaluation methods varied between studies [22,23].…”
Section: Introductionmentioning
confidence: 99%